The doctrine of implied powers of international organizations in the case law of international tribunals - Gadkowski, Andrzej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The aim of this article is to present the contribution of international tribunals to the development of the doctrine of implied powers of international organizations. The author discusses the case law and the position presented by the PCIJ and the ICJ regarding the powers of international organizations. He points to the basis for implication of powers of international organizations and the limitation of such implication and presents a noticeable evolution of the tribunals view on the issue of implied powers.